Ethical Leadership And Employee Performance: The Mediating Role Of Motivation At PT PLN (Persero) Lampung Distribution Main Unit - Lispiansi Lestari; Ayi Ahadiat; Zainnur M. Rusdi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effect of ethical leadership on employee performance and investigates the mediating role of motivation at PT PLN (Persero) Unit Induk Distribusi Lampung. Ethical leadership has become increasingly important in organizational management because leaders are expected not only to achieve organizational goals but also to demonstrate fairness, integrity, and concern for employee welfare. Despite continuous efforts to improve organizational performance, employee performance achievements remain inconsistent and are accompanied by variations in employees’ perceptions of ethical leadership practices This study employed a quantitative cross-sectional survey design. Data were collected from employees of PT PLN (Persero) Unit Induk Distribusi Lampung using a structured questionnaire with a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Ethical leadership was measured through fairness, integrity, ethical guidance, people orientation, power sharing, role clarification, and concern for sustainability. Motivation and employee performance were measured using established indicators adopted from previous studies.Grounded in Social Learning Theory and Social Exchange Theory, this study proposes that ethical leadership directly influences employee performance and indirectly affects performance through motivation. Ethical leaders serve as role models whose fair and trustworthy behavior encourages employees to reciprocate through higher motivation and better work performance. The findings are expected to enrich the literature on ethical leadership and provide practical implications for leadership development and human resource management strategies aimed at improving employee performance in public service organizations.